Type I interferon shapes the quantity and quality of the anti‐Zika virus antibody response - Lee, Cheryl Yi‐Pin (Clin Transl Immunology, 2020)
OBJECTIVES: Zika virus (ZIKV) is a mosquito‐borne flavivirus that re‐emerged in 2015. The association between ZIKV and neurological complications initiated the development of relevant animal models to understand the mechanisms underlying ZIKV‐induced pathologies. Transient inhibition of the type I interferon (IFN) pathway through the use of an IFNAR1‐blocking antibody, MAR1‐5A3, could efficiently permit active virus replication in immunocompetent animals. Type I IFN signalling is involved in the regulation of humoral responses, and thus, it is crucial to investigate the potential effects of type I IFN blockade towards B‐cell responses. METHODS: In this study, comparative analysis was conducted using serum samples collected from ZIKV‐infected wild‐type (WT) animals either administered with or without MAR1‐5A3. RESULTS: Serological assays revealed a more robust ZIKV‐specific IgG response and subtype switching upon inhibition of type I IFN due to the abundance of antigen availability. This observation was corroborated by an increase in germinal centres, plasma cells and germinal centre B cells. Interestingly, although both groups of animals recognised different B‐cell linear epitopes in the E and NS1 regions, there was no difference in neutralising capacity. Further characterisation of these epitopes in the E protein revealed a detrimental role of antibodies that were generated in the absence of type I IFN. CONCLUSION: This study highlights the role of type I IFN in shaping the anti‐ZIKV antibody response to generate beneficial antibodies and will help guide development of better vaccine candidates triggering efficient neutralising antibodies and avoiding detrimental ones.